The emerging role of cuproptosis in spinal cord injury - Xu, Daoran; Hu, Liyu; Zhou, Jinming; Deng, Xiongwei; Zhu, Yunrong; Liu, Chao (Frontiers in Immunology, 2025)
Copper is a vital trace element integral to numerous biological processes, including iron metabolism, neurotransmitter synthesis, mitochondrial respiration, oxidative stress regulation, and energy production. However, disturbances in copper metabolism can result in pathological conditions, including cuproptosis—a newly recognized form of programmed cell death (PCD) marked by copper accumulation and the disruption of copper-dependent metabolic pathways. Cuproptosis has been associated with various diseases, such as cancer, metabolic disorders and neurodegenerative disorders. In the context of spinal cord injury (SCI), multiple pathological mechanisms, including oxidative stress, inflammation, and PCD could impact the patient’s prognosis with SCI. This review seeks to elucidate the pathophysiological underpinnings of SCI, the mechanisms and biological significance of copper homeostasis and the role of cuproptosis in SCI.